PENGARUH SUKU BUNGA KREDIT DAN DEPOSITO BANK KONVENSIONAL TERHADAP MARGIN PEMBIAYAAN MURABAHAH BANK SYARIAH DI INDONESIA - Mohammad Hasan Bisyri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2015)
This study seeks to uncover the MUI fatwa from the progressive aspects of Islamic law. Fatwa is the mirror of the dynamics of Islamic law in responding to the development of society. The set of MUI fatwa, in addition to functioning as a reference source of religious guidance, are also a historical record that is a source of social history. Fatwa ideally is always dynamic and paying attention to the dynamics of reality in society. Results of this study indicate that in general the MUI fatwa still had not moved from the tradition of jurisprudence, MUI fatwa is more nuanced as the social control and social engineering.